Kashmir's contested pasts narratives, sacred geographies, and the historical imagination - Zutshi, Chitralekha 1972- (Oxford University Press, 2014)
This volume explores the idea of Kashmir and the idea of history, and their articulation in tandem within Kashmir's multilingual historical tradition. It illuminates the multiple definitions of Kashmir as a sacred space and polity, and history as a tradition and a set of facts. It reflects on the historical memories and practices that have informed imaginings of Kashmir and its past, and the challenges posed to these ideas in Kashmiri political culture today.